Joint position and general hypermobility affect elbow joint congruence on magnetic resonance imaging: a prospective cohort study - Geyer, Stephanie; Hinz, Maximilian; Kadantsev, Pavel; Lappen, Sebastian; Winkler, Philipp W.; Neumann, Jan; Schwaiger, Benedikt J.; Siebenlist, Sebastian (The American journal of sports medicine, 2025)
Background: Patients with posterolateral rotational instability (PLRI) of the elbow exhibit a higher degree of joint incongruence on magnetic resonance imaging (MRI) than patients without PLRI. However, the influence of joint hypermobility and position of the elbow in healthy participants is yet unknown. - Purpose: To analyze the influence of general hypermobility and elbow joint position on joint congruence in healthy participants via MRI. - Study Design: Case-control study; Level of evidence, 4. - Methods: Twenty participants with Beighton score <5 (normal group) and 20 with Beighton score ≥5 (hypermobile group) who had healthy elbows underwent bilateral MRI in full extension and supination, full extension and pronation, and 30° of flexion in both supination and pronation. Sagittal radiocapitellar joint incongruence and ulnohumeral joint incongruence (in sagittal, coronal, and axial planes) were measured according to a standardized protocol. - Results: Radiocapitellar congruence increased in pronation (P < .001) but did not change between flexion and extension (P > .05). Coronal ulnohumeral congruence increased significantly from extension and supination to pronation (P = .010) and to combined flexion and pronation (P = .011). Sagittal and axial ulnohumeral joint congruence did not change significantly between different elbow joint positions (P > .05). Significant differences between the normal and hypermobile groups were observed in 3 of the 4 evaluated joint positions. Overall, the hypermobile group showed an increased joint incongruence except in extension and pronation (P > .05). - Conclusion: In MRI examination of healthy elbows, joint congruence increased significantly from supination to pronation. In combined extension and pronation, the elbow joint was equally congruent in the normal and hypermobile groups. When MRI scans in supination or combined flexion and pronation are evaluated, increased joint incongruence in hypermobile individuals is physiological and should not be confused with PLRI.
Online veröffentlicht: 15. April 2025
Gesehen am 02.10.2025